Empty follicle syndrome: A challenge to physician - Neeta Singh; Venus Dalal; Alka Kriplani; Neena Malhotra; Reeta Mahey; Vanamail Perumal (Wolters Kluwer Medknow Publications, 2018)
Background: Empty follicle syndrome (EFS) is a condition in which no oocytes are retrieved from normally growing ovarian follicles after ovarian stimulation. It is a rare and frustrating condition of obscure etiology. Objective: The objective of this study was to estimate the incidence of EFS and study factors related to it. Design: This was a retrospective study. Setting: This study was conducted in hospital-based research center. Methods: In 1968 in vitro fertilization cycles from January 2010 to August 2016 were studied. Agonist, antagonist, and miniflare protocols were used for the stimulation. Results: The incidence of EFS is 2.38% (47/1968 cycles). Antagonist protocol group (76.59%, n = 36) had highest incidence of EFS (6.69%). Literature on EFS depicts decreased ovarian reserve (DOR) as the main cause, but only 4.25% of patients had DOR in our study. Interestingly, polycystic ovary syndrome and unexplained infertility were found in 31.9% of the cases. Serum anti-Müllerian hormone (AMH) levels (mean ± standard deviation [SD]) were 4.47 ± 3.54 ng/ml, and antral follicle count (AFC) was 15.30 ± 8.07 (mean ± SD) emphasizing that diminished ovarian reserve is not the main factor for EFS. All patients (n = 95) who underwent ovum pickup on day when any patient had EFS were taken as control. Patients with EFS were compared with controls. A statistically significant difference was not observed in serum AMH (P = 0.38) and AFC (P = 0.52). Conclusion: EFS is an uncommon event. Antagonist cycles have higher chances of empty follicle at ovum pickup. Looking at the profile of patients in this study, we conclude that EFS is not a manifestation of DOR.